2012
DOI: 10.1007/s00232-012-9502-y
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Inhibits Outward Voltage-Gated K+ Currents in Human Osteoblast-Like MG63 Cells

Abstract: Previous studies have shown that 17β-estradiol has a pivotal function by blocking voltage-gated K⁺ (Kv) channels in several different types of cells such as cardiac myocytes and neurons. Outward Kv currents can also be measured in osteoblasts, although little is known about the effects of 17β-estradiol on these currents. In human osteoblast-like MG63 cells, we found that 17β-estradiol inhibits peak and end Kv currents, with IC₅₀ values of 480 and 325 nM, respectively. To elucidate the mechanism of inhibition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Estradiol has many other effects, including inhibitory effects on Kv channel activity (Li et al.,. ,,2013, 2014), which we would predict would enhance spontaneous release. Therefore, it is unclear if estrus effects in female mice used here in contributing to spontaneous DA release since estradiol could have opposing effects on the same circuit.…”
Section: Discussionmentioning
confidence: 73%
“…Estradiol has many other effects, including inhibitory effects on Kv channel activity (Li et al.,. ,,2013, 2014), which we would predict would enhance spontaneous release. Therefore, it is unclear if estrus effects in female mice used here in contributing to spontaneous DA release since estradiol could have opposing effects on the same circuit.…”
Section: Discussionmentioning
confidence: 73%
“…To date, little is known about the role of K V channels in MG-63 and Saos-2 cells. Although several studies confirmed the existence of TEA-sensitive [ 66 ] or K V 2.1-related outward K V currents [ 67 ], and the existence of K V 7 channels has been demonstrated in MG-63 cells [ 23 ], the physiologic functions of K V 7 channels in MG-63 and Saos-2 cells are not widely known. In the present study, we identified the mRNA and protein expression of K V 7.3 channels in MG-63 and Saos-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, K ATP channels in different brain regions, including the hippocampus, may participate in the process of neuroprotection through counteracting ischemia and Aβ neurotoxicity. (Saito et al, 2009;Tsang et al, 2004) -No (Wong et al, 2008) Kv2.1 Downregulation (El Gebeily and Fiset, 2011) -Inhibition (Druzin et al, 2011;Li et al, 2013) Kv2.2 -Inhibition (GPR30-mediated PKC pathway) (Dong et al, 2013) Inhibition (Druzin et al, 2011) Kv4 Intriguingly, increasing evidence indicates that estrogens also produce a regulatory action in K ATP channels. In GnRH neurons important to the control the female reproductive cycle, 17βestradiol enhances the activity of K ATP channels via a membrane ER-activated PKC-PKA signaling pathway, without affecting the mRNA levels of the Kir6.2 and SUR1 subunits (Zhang et al, 2007;Zhang et al, 2010).…”
Section: K Atp Channelsmentioning
confidence: 99%
“…Hence, Kv2.1 channels are closely associated with neuroprotective effects owing to their ability to regulate the excitability and apoptosis of neurons. Acute exposure to 17β-estradiol significantly blocks Kv2.1-dominated outward Kv currents in human osteoblast-like MG63 cells and Kv2.1 channels reconstituted in COS-7 cells, with an IC 50 of 0.3 μM ( Li et al, 2013 ). Corresponding with this report, Kv2.1- and Kv2.2-mediated Kv currents are also inhibited by acute application of 17β-estradiol in the medial preoptic nucleus (MPN), with an EC 50 value of 9.7 μM ( Druzin et al, 2011 ).…”
Section: Kv Channelsmentioning
confidence: 99%